The modified inframammary fold suture method and its clinical significance in primary augmentation mammoplasty. (14th October 2022) - Qin, Feng; Zeng, Ang; Yu, Nanze; Dong, Ruijia; Long, Fei; Xia, Zenan; Zhang, Wenchao; Long, Xiao; Wang, Xiaojun
Abstract: Background: The inframammary approach is one of the most commonly used incisions in breast augmentation. There are many suture methods for inframammary incisions; however, no one method has proven optimal. We modified the traditional three‐layer suture method according to the inframammary fold (IMF) cadaver dissection results. This study aims to investigate whether using a modified suture method can improve postoperative outcomes. Methods: Cadaver dissections were performed in order to clarify the anatomy of the IMF. From June 2013 to December 2017, a retrospective study of primary breast augmentation patients subjected to the inframammary approach was conducted. Patients were divided into two cohorts: the traditional suture method and the modified suture method. The patient's demographics, specifics of breast augmentation procedures, complications, and scar assessment were analyzed. Univariate and multivariable analyses were used to determine differences between the two cohorts. Results: One hundred eighty‐four patients were included: 75 patients were subjected to the traditional suture method, and 109 patients were subjected to the modified suture method. Wound‐related adverse events ( p  = 0.026) and IMF‐indented scarring ( p  = 0.014) were significantly different between the two groups. Multivariable analysis showed that the suture method was the most influential factor related to IMF‐indented scarring (OR = 16.9), followed by BMI (OR = 2.9). Conclusions: We defined a new suture method for the inframammary incision in primary breast augmentation. This modified suture method reduces the occurrence of wound‐related adverse events and IMF‐indented scarring.